Intercropping as a component in insect pest management for grain cowpea, Vigna unguiculata Walp production in Nigeria - Alghali, A.M. (1993)
A series of experiments involving plots of sole cowpea and sorghum/cowpea intercrops were carried out, on-farm, in Minjibirr village, northern Nigeria between 1986 and 1988. The objectives were to: (1) elucidate the relationships between sorghum/cowpea Intercropping, insect pest numbers and grain yield reductions in cowpea. (2) examine the role of sorghum/cowpea intercropping alone or together with reduced Insecticide usage in the management of cowpea insect pests. Different cowpea varieties were grown under both cropping systems in sprayed and unsprayed plots. The insecticides used were Sherpa Plus and/or Cymbush Super ED. Intercropping reduced the numbers of flower thrips and pod sucking bugs, but made no difference to the numbers of pod borers. Unprotected sole crop and Intercropped cowpea had yields reduced by 55 and 48% respectively, compared to sprayed subplots. The best results were obtained with three Insecticldal sprays, which increased grain yields 4.5-fold. Intercropping with two sprays produced lower, but comparable yields. Thus, it is suggested that intercropping can be used with reduced insecticide levels for the effective management of cowpea insect pests.